PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KEMAMPUAN MENYAJIKAN TARI PENDEK BERTEMA PADA SISWA KELAS III SD MUHAMMADIYAH 4 PEKANBARU - Noviana, Eddy Noviana Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : background of this study is the low of the third grade students to present dance with themes of SD Muhammadiyah 4 Pekanbaru,with is avarage score of class is 57. Based on standard minimum criteria (KKM) 70, which is has been determined by school. There were 14 students are below the standard criteria and 6 students are above the minimum standard criteria from overal number of 20 students. This research is an action research which aim to increase the talent of student to present short dance with themes and apply direct learnin. Formulation of the problem :Does model direct learning can increase the talent of to present short dance with themes of class III SD Muhyammadiyah 4 Pekanbaru. This research was carried out on October until November month with II cycles. The subject of this research is the third grade of students in SD Muhammadiyah 4 Pekanbaru with 20 students Who were become the participants of this research. Data collection instruments in this research are theacher’s activities and rating of criteria. Result of this research can be seen from the result of the study before the implamantition of direct learning is 57after the action of direct learning, the avarage getting increased in cycle I. Become 61 which are increased as much as 7 %, and cycle II the avarage score 91 which are increased as much as 49 %. It can be concluted that the models of direct learning can increased the talented of the third grade student in SD Muhammadiyah 4 Pekanbaru.Keywords : Direct learning model, the talent to present short dance